THE CORRELATION BETWEEN PARENTS’ EDUCATION AND EARLY CHILDHOOD EDUCATION ENROLMENT DECISIONS - Ulfa, Yostiana Bella; Djamaluddin, Sartika (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
Early Childhood Education (ECE) is crucial for a child’s school readiness, development, welfare, and future academic achievement. However, Indonesia is currently facing low participation of ECE students. This study discusses the parents’ education, household characteristics, child development, infrastructure, and environmental characteristics associated with parents’ decisions on ECE enrolment. This study uses a quantitative approach with probit regression. The data used for this research were from the 2020 Indonesia’s National Socio-Economic Survey and Village Potential Survey. The results of this study indicated that parents’ education had a positive and significant correlation with the parent’s decision to send their children to ECE. The income per capita, the mother's job status, the father's job status, access to food for the household, and the number of household members, which are household characteristics, determine ECE enrolment decisions. Children's growth and development, the infrastructure of the ECE within the district/city, and the environmental characteristics such as residential classification and the regional area of residence are proven to be associated with ECE enrolment.